2023
DOI: 10.5194/hess-27-3221-2023
|View full text |Cite
|
Sign up to set email alerts
|

Calibration of groundwater seepage against the spatial distribution of the stream network to assess catchment-scale hydraulic properties

Ronan Abhervé,
Clément Roques,
Alexandre Gauvain
et al.

Abstract: Abstract. The assessment of effective hydraulic properties at the catchment scale, i.e., hydraulic conductivity (K) and transmissivity (T), is particularly challenging due to the sparse availability of hydrological monitoring systems through stream gauges and boreholes. To overcome this challenge, we propose a calibration methodology which only considers information from a digital elevation model (DEM) and the spatial distribution of the stream network. The methodology is built on the assumption that the groun… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 121 publications
2
5
0
Order By: Relevance
“…The transmissivities and associated hydraulic conductivities estimated in this study are consistent with values obtained from hydraulic tests or numerical groundwater models carried out in the similar region and lithological context (BRGM, 2018;Jiménez-Martínez et al, 2013;Kolbe et al, 2016;Le Borgne et al, 2006). More precisely, we find the same order of magnitude of K at 10 À5 m/s as in other studies carried-out on the Nançon catchment (Abhervé et al, 2023;Cornette et al, 2022;Dewandel et al, 2021) and the Canut catchment (Abhervé et al, 2023). The low porosity values estimated are consistent with the values found in the literature in crystalline bedrock contexts (Leray et al, 2012;Roques, 2013;Singhal & Gupta, 2010;Wyns et al, 2004).…”
Section: Use Of Streamflow Intermittence Information To Estimate Aqui...supporting
confidence: 91%
See 4 more Smart Citations
“…The transmissivities and associated hydraulic conductivities estimated in this study are consistent with values obtained from hydraulic tests or numerical groundwater models carried out in the similar region and lithological context (BRGM, 2018;Jiménez-Martínez et al, 2013;Kolbe et al, 2016;Le Borgne et al, 2006). More precisely, we find the same order of magnitude of K at 10 À5 m/s as in other studies carried-out on the Nançon catchment (Abhervé et al, 2023;Cornette et al, 2022;Dewandel et al, 2021) and the Canut catchment (Abhervé et al, 2023). The low porosity values estimated are consistent with the values found in the literature in crystalline bedrock contexts (Leray et al, 2012;Roques, 2013;Singhal & Gupta, 2010;Wyns et al, 2004).…”
Section: Use Of Streamflow Intermittence Information To Estimate Aqui...supporting
confidence: 91%
“…In fact, we found that a non‐unique solution exists when only streamflow is considered, which poses a challenge in selecting a representative set of parameters. As already shown in Abhervé et al (2023), the extent of the stream network provides a constraint on groundwater level, allowing us to estimate the T/R$$ T/R $$ ratio, and hence K$$ K $$ by making assumptions on d$$ d $$ and R$$ R $$. Here, the approach is developed/extended in transient where the estimation of porosity relies on both the streamflow and the expansion/contraction of the hydrographic network.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations